(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
This study focuses on establishing a fast and novel RP-HPLC method along with its comparable UV spectroscopic approach for the routine evaluation of montelukast sodium. Using Design Expert software, a 3² full-factorial design was deployed to optimize the RP-HPLC method. Retention time, tailing factor, and theoretical plate count were considered as the dependent response parameters in this design, and the mobile phase composition and its flow rate were chosen as the independent variables. A mobile phase composed of methanol and water (40:60, %v/v) was eluted through a C18 column (250 × 4.6 mm, 5 μm) at a flow rate of 1.0 mL/min for the chromatographic separation. The wavelength used for detection was 344.4 nm to ensure optimal sensitivity for the analyte. The RP-HPLC method development yielded statistically significant models (p<0.05). The proposed method was validated in accordance with ICH standards. Retention time of the drug was found to be 5.009 minutes. A linear calibration curve was obtained over the concentration range of 40-60 μg/mL. The method demonstrated a limit of detection of 0.15 μg/mL and a limit of quantification of 0.50 μg/mL. Additionally, a UV spectroscopic method was also developed and validated, showing comparable results to the RP-HPLC method (p<0.05). Overall, the developed RP-HPLC method along with its comparable UV spectroscopic method demonstrated a comprehensive approach for the routine analysis of montelukast sodium. Dhaka Univ. J. Pharm. Sci. 24(2): 197-209, 2025 (December)